2011
DOI: 10.1542/peds.2010-1722r
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Beliefs of Parents Concerned About Vaccines: Impact of Timing of Immunization Information

Abstract: OBJECTIVES:To determine if giving vaccine-information materials before the 2-month vaccination visit to mothers with concerns about vaccine safety positively changed their attitudes and beliefs about vaccine safety. METHODS:Mothers who indicated concerns about infant vaccinations were recruited from 2 separate sites in Tennessee and California and were given vaccine information at 1 of 3 times: during a prenatal visit; a 1-week postpartum well-child visit; or a 2-month vaccination visit. A separate group of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
59
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 17 publications
9
59
1
3
Order By: Relevance
“…Consistent with prior research, 22,23 most respondents indicated that talking to a physician or reading an information sheet would be helpful for making a decision about HPV vaccination, although parents who reported refusal less often perceived these resources to be helpful. We were encouraged to note that, across respondent groups, relatively few parents believed that providers should never routinely recommend HPV vaccine.…”
Section: Discussionsupporting
confidence: 68%
“…Consistent with prior research, 22,23 most respondents indicated that talking to a physician or reading an information sheet would be helpful for making a decision about HPV vaccination, although parents who reported refusal less often perceived these resources to be helpful. We were encouraged to note that, across respondent groups, relatively few parents believed that providers should never routinely recommend HPV vaccine.…”
Section: Discussionsupporting
confidence: 68%
“…One study reported that the majority of mothers preferred receiving vaccine information before the initial immunization visit. 65 The provision of a VIS is required at each immunization encounter for each vaccine, and counseling about vaccine-preventable diseases and vaccine adverse effects is required to correctly bill for vaccine administration. If parents refuse vaccination, a vaccine refusal waiver, used by many pediatricians in the event of deviations from the recommended vaccine schedule, can be obtained from the AAP Web site (https:// www.…”
Section: The Current Vaccine Schedule Is the Only Recommended Schedulementioning
confidence: 99%
“…43 Using this style, the physician can discuss both the vaccine and disease risks and benefits, supported by easily digestible written and online resources. 24,38,44,45 It is possible for a recommendation to vaccinate be included with such an approach.…”
Section: Vaccination Uptakementioning
confidence: 99%